Suprapubic single-incision laparoscopic right colectomy with complete mesocolic excision, lateral-to-medial approach and intracorporeal anastomoses - Giovanni Dapri; Kelly Ann Bobb; Ernesto Jesús Barzola Navarro; Angel Arabadzhiev (Society of Gastrointestinal Intervention, 2019)
Background : Single-incision laparoscopic right colectomy (SILRC) has been reported in 2008, and since that time an increased number of reports appeared in literature. Currently, it remains popular between the centers with achieved experience. Adoption of suprapubic access, instead of umbilical or other access-sites, allows to enhance the final cosmetic outcomes, together with the realization of complete mesocolic excision (CME) and intra-corporeal anastomosis (ICA). Methods : Between January 2016 and August 2018, 20 patients (10 females, 10 males) were submitted to suprapubic single-incision laparoscopic right colectomy (SSILRC) for adenocarcinoma. Mean age was 74 years and mean body mass index was 24 kg/m2. Sixteen patients have already been submitted to open abdominal surgery. Results : Mean total operative time was 233.9 minutes and mean laparoscopic time was 199.4 minutes. Mean time for ICA was 34 minutes. Mean blood loss was 279.5 mL. One additional 5-mm trocar was necessary in 1 patient (5.0%). Mean length scar was 60.5 cm. Mean hospital stay was 7.8 days. A minimal use of pain killers was registered postoperatively. Mean number of lymph nodes retrieved was 24.5. Early complications were one suprapubic abscess and one suprapubic hematoma. No late complications, including suprapubic incisional hernia, were achieved. Conclusion : Since the specimen has to be removed from the abdomen after conventional laparoscopic right colectomy, the suprapubic access can be an option. SSILRC allows to join the surgical procedure, the specimen's removal and the enhanced cosmetic results through the same access. Other advantages are the CME, the ICA, the reduced postoperative pain, and the decreased incisional hernia's rate.